Brevianthrones, bianthrones from a Chinese isolate of the endophytic fungus Colletotrichum brevisporum. (August 2021) - Lin, Min; Adpressa, Donovon A.; Feng, Meiyu; Lu, Ya; Clark, Benjamin R.
Abstract: Seven undescribed bianthrones, the brevianthrones, together with two known anthraquinones, were isolated from the plant-derived fungus Colletotrichum brevisporum, obtained from the plant Piper sarmentosum Roxb., collected in Guangxi, China. This is the first report of the isolation of bianthrones from the Colletotrichum genus. The structures of the compounds were elucidated by a combination of NMR and MS spectroscopic analysis, while the absolute configurations were determined by X-ray crystallography and by simulation of ECD spectra. Graphical abstract: Image 1 Highlights: Seven undescribed bianthrones were obtained from plant-derived fungus. First report of chemical investigation of Colletotrichum brevisporum . Absolute configurations assigned based on X-ray diffraction and ECD simulation.